Flipping and gamifying university’s online English preparation courses: Understanding learner flow state and autonomy - Safnil Arsyad; Budi Waluyo; Leffi Noviyenty; Amrullah Amrullah; Paidi Gusmuliana; Rismar Riansih (Universitas Syiah Kuala, 2026)
This study utilized a sequential exploratory mixed methods design to examine the synergistic effects of flipped and gamified learning on students’ flow state and autonomy in a fully synchronous online English preparation course at an Indonesian university. Through a narrative approach and a one-group pretest-post-test design, the research engaged 25 undergraduates, incorporating technology both inside and outside the classroom. Data collection consisted of narrative frames over two cycles, surveys, teachers’ observations, and analytics from gamification apps, all of which were analyzed using thematic analysis alongside descriptive and inferential statistics. Results indicated that these innovative teaching strategies significantly improved student motivation and autonomy by fostering an interactive environment that synergized skill improvement with challenge and provided real-time feedback. These methodologies improved listening and reading scores, but advancements in structural knowledge and written expression were less pronounced, suggesting a need for more focused pedagogical tactics. Qualitative data demonstrated high engagement levels, yet they accentuated a complex interplay between motivation and academic performance, emphasizing the critical roles of technological accessibility and comprehensive teacher training in maximizing learning outcomes across various competencies. This study highlights the necessity of addressing technological and instructional barriers to fully leverage the benefits of flipped and gamified learning environments.